Changes of oxygen-containing groups during thermal treatment and their influences on moisture readsorption of lignite. Issue 6 (25th April 2016) - Jing, Xiaoxia; Li, Zhiqiang; Zhang, Yanli; Chang, Liping
ABSTRACT: The changes in oxygen-containing groups in the thermal treatment process of lignite were analyzed and the moisture readsorption amounts of upgraded coals were related in this study. A chemical titration method was applied to determine the types and contents of oxygen-containing groups in raw lignite and upgraded coals obtained in the temperature range of 353–633 K under atmospheres of argon, air, and carbon dioxide. Experimental results showed that the oxygen-containing groups mainly involved carbonyl, phenolic hydroxyl, and carboxylic groups (including carboxyl and carboxylate), among which phenolic groups were dominant. These different oxygen-containing groups decomposed discriminatingly with temperature according to thermal stability. The removal of oxygen-containing groups proceeded more easily in a CO2 atmosphere compared to in Ar. The oxidation reaction occurring on the surface of lignite exposed to air led to an increase in oxygen-containing groups. The different types of oxygen-containing groups possessed various combining abilities with water, among which carboxyl was considered the most important group for the moisture readsorption. Decomposition of oxygen-containing groups in the thermal treatment process of lignite mainly caused a reduction in monolayer water adsorption and further decreased the multilayer water.